Kajian Hadis di Lingkungan Nahdlatul Ulama dan Muhammadiyah - Muhammad Ali; Bunganegara, Muadilah Hs. (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2023)
This discussion is related to the study of hadith in the religious institutions of Nahdlatul Ulama and Muhammadiyah which are the two major religious institutions in Indonesia. This article will focus on how the study of hadith in the Nahdlatul Ulama and Muhammadiyah circles. Therefore, it is necessary to conduct studies and presentations as a form of description related to hadith studies within the Nahdlatul Ulama and Muhammadiyah by conducting historical studies based on literary sources. So it was found that there was a significant difference in the effort to use hadith when making a determination of a law. Within the Nahdlatul Ulama environment, it is more tolerant of the use of daif hadiths when it comes to charitable activities. Whereas in the Muhammadiyah environment, priority is given to the use of hadiths that have been agreed to be used as a basis. . Keywords; Hadith studies; Nahdlatul Ulama; Muhammadiyah